Surā maichai sinkhā thammadā : rīanrū panhā čhāk kō̜ranī tok pen khāo - Čhuthāphō̜n Kǣomungkhun (Sūn Wičhai Panhā Surā, 2007)
Compilation of news on crimes and violence resulting from alcohol consumption.